1997
DOI: 10.1007/s004649900466
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy and time-course changes in renal function

Abstract: Our findings demonstrate that reduction of IAP to 4 mmHg using the retraction method prevents the transient renal dysfunction caused by prolonged 12 mmHg pneumoperitoneum during LC, suggesting that the retraction method reduces the risk of perioperative renal dysfunction during laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 10 publications
0
24
0
2
Order By: Relevance
“…Only a few studies of renal function at 12 mmHg or less of CO 2 PP have been published. Various species, pressure levels of PP, and procedures have been studied, and the results generally show a decrease in renal function and an increase in vasopressin levels [5,8,9,10,16,17]. Interestingly, one study showed that a vasopressin antagonist decreased the renal effects [1].…”
mentioning
confidence: 99%
“…Only a few studies of renal function at 12 mmHg or less of CO 2 PP have been published. Various species, pressure levels of PP, and procedures have been studied, and the results generally show a decrease in renal function and an increase in vasopressin levels [5,8,9,10,16,17]. Interestingly, one study showed that a vasopressin antagonist decreased the renal effects [1].…”
mentioning
confidence: 99%
“…However, there is compelling evidence that the pneumoperitoneum reduces renal blood flow [3,9,10,18]. In addition, compared with open surgery, endoscopic dissection techniques require longer surgical manipulation in the vicinity of the renal artery, potentially causing arteriospasm.…”
Section: Discussionmentioning
confidence: 98%
“…In a review of five animal studies, Shafer, et al demonstrated a decrease in renal perfusion ranged from 12% to 14% [14]. Miki, et al reported a decreased urine output and GFR in patients after laparoscopic cholecystectomy, whereas no significant changes in these parameters were observed when an abdominal lift device was used [15].…”
Section: Conflict Of Interestmentioning
confidence: 99%